“This Rude Chivalry of the Wilderness”: Chivalry and Native Americans in Cooper’s and Irving’s American Novels - Pauline Pilote (Perspectives Médiévales)
“In the four quarters of the globe, who reads an American book?” This oft-quoted sentence actually comes from a review written by Sidney Smith in January 1820 for the Edinburgh Review of Adam Seybert’s book, Statistical Annals of the United States of America. Yet this text also follows, in the same issue, an article reviewing the whole of Scott’s texts that had been so far published and which quotes lengthy excerpts from the latest romance, Ivanhoe. This book in particular, which takes medieval England as its background, was probably one of the most widely read of the Waverley Novels in America. The enthusiasm of the American readership in the early decades of the 19th century seems to reveal a general attraction for the European Middle Ages. Indeed, Scott’s American contemporaries resort to the medieval apparatus that was brought back into fashion by Ivanhoe – stereotypes of knight-errantry, damsels in distress, code of honour, etc. – to describe the Native Americans that people their narratives. Both Cooper – the “American Scott” – and Washington Irving thus transplant medieval features onto the wilderness, thereby presenting the New World as a land calling for chivalric feats, paradoxically endowing that supposed pristine landscape with a general atmosphere of romance.